Impaired toll-like receptor signalling in peripheral B cells from newly diagnosed type-2 diabetic subjects. Issue 2 (December 2015) - Madhumitha, Haridoss; Mohan, Viswanathan; Kumar, Nathella P.; Pradeepa, Rajendra; Babu, Subash; Aravindhan, Vivekanandhan
Highlights: Reduced TLR expression in the B cells in newly diagnosed diabetic (NDD) subjects. TLR induced TNF-α and IL-6 secretion impaired in NDD subjects. TLR induced B cell activation is defective in NDD subjects. Signalling defect not due to apoptosis or secretion of immunosuppressive cytokines. Signalling defect was ameliorated in the known diabetic group under treatment. Abstract: Toll-like receptors (TLRs) under diabetic conditions trigger inflammation and impair immunity. In the present study, we looked at the expression of TLRs (2 and 4) and their adaptors in Normal Glucose Tolerant (NGT), Newly Diagnosed Type-2 Diabetic (NDD) and Known Type-2 Diabetic (KDM) subjects. We also estimated TLR induced cytokine secretion, cellular activation and apoptosis. Surface expression of TLR2 and 4 was significantly reduced in the B cells of the NDD subjects and was associated with decreased cellular activation and cytokine secretion (TNF-α and IL-6). This impairment was not due to B cell deficiency or apoptosis or immunosuppressive cytokine (IL-10 and TGF-β) secretion. However, the upregulation of immunomodulatory enzymes (Arg-1, HO-1 and IDO) could probably account for the reduced TLR expression. The defective TLR signalling was largely ameliorated in the KDM group which might be due to the use the anti-diabetic drugs which have anti-inflammatory effect.